Analysis on the Common Quality Problems and Production Methods of Jeans Belt Loop Knot - Huo, Yarui; Faridah, Sahari (Bio-Byword Scientific Publishing Pty. Ltd., 2022)
The belt loop is an important part of a standard five-pocket jThe belt loop is an important part of a standard five-pocket jeans, integrating functionality and aesthetics. Because of common problems such as skewed belt loop, unequal lengths, improper slackness, double lines at the front pocket of the belt loop cover, exposed bottom of the belt loop, asymmetry, too low or too high position of the belt loop, and no light in the back, we tracked the sewing of the belt loop in the jeans production line, analyzed the causes of the problems, and came out with targeted solutions. We analyzed the operation steps of knotting jeans belt loops and then develop daily maintenance measures for knotting machines, provide technical guidance for seamstresses/seamsters and team leaders to enhance the maintenance ability to knot machines, enhance the ability of knotting machines to run well, ensure the stability of jeans belt loops quality, and provide technical reference for quality control of belt loops in the same type of jeans production lines